Performance Analysis of Maximal Ratio Transmission with Relay Selection in Two-way Relay Networks Over Nakagami-m Fading Channels - Erdogan, Eylem; Gucluoglu, Tansal (SPRINGER, 2016)
In this paper, we investigate the performance of an amplify-and-forward multi-input multi-output two way relay network where two sources are equipped with multiple antennas employing maximal ratio transmission and the communication is carried through the selected relay resulting in the largest received power. Assuming the fading channel coefficients are Nakagami-m distributed, we derive the sum symbol error rate (SSER), outage probabilities for each user and the overall system. In addition, diversity and array gains are obtained using the derived asymptotic SSER and system outage probability (OP) expressions. With the help of asymptotic system OP, we find the optimum location of relay by solving the convex optimization problem. Furthermore, we investigate the impact of limited feedback and imperfect channel estimations on the performance of the proposed structure. Finally, theoretical findings are validated by simulation results.
Keywords: Two-way relay network; Maximal ratio transmission; Relay selection; Sum symbol error rate; System outage probability; AMPLIFY-AND-FORWARD; EFFICIENT PROTOCOLS; ANTENNA; Telecommunications